Managerial effectiveness - Reddin, W. J. (New York : McGraw-Hill, 1970)
The aim of this book is to make managers and the organizations they work in more effective. The book allows the manager to make a value analysis of himself in the organization. It also gives him direct advice on how to improve his own effectiveness and that of others.
Includes bibliographical references p.331-339.and index
hza 09/08/2018
Loans
Keywords: Management; Executive ability